CD8+γδ T Cells Are More Frequent in CMV Seropositive Bone Marrow Grafts and Display Phenotype of an Adaptive Immune Response - Ahmed Gaballa; Lucas C. M. Arruda; Emelie Rådestad; Michael Uhlin (Hindawi Limited, 2019)
The role of gamma delta (γδ) T cells in human cytomegalovirus (HCMV) immune surveillance has been the focus of research interest for years. Recent reports have shown a substantial clonal proliferation of γδ T cells in response to HCMV, shedding light on the adaptive immune response of γδ T cells. Nevertheless, most efforts have focused on Vδ2negγδ T cell subset while less attention has been given to investigate other less common γδ T cell subsets. In this regard, a distinct subpopulation of γδ T cells that expresses the CD8 coreceptor (CD8+γδ T cells) has not been thoroughly explored. Whether it is implicated in HCMV response and its ability to generate adaptive response has not been thoroughly investigated. In this study, we combined flow cytometry and immune sequencing of the TCR γ-chain (TRG) to analyze in-depth bone marrow (BM) graft γδ T cells from CMV seropositive (CMV+) and CMV seronegative (CMV-) donors. We showed that the frequency of CD8+γδ T cells was significantly higher in CMV+ grafts compared to CMV- grafts (P<0.001). Further characterization revealed that CD8+γδ T cells from CMV+ grafts express Vγ9- and preferentially differentiated from a naive to terminal effector memory phenotype (CD27low/-CD45RO-). In line with these findings, TRG immune sequencing revealed clonal focusing and reduced usage of the Vγ9/JP gene segment in a CMV+ graft. Furthermore, CD8+γδ T cells showed an enhanced response to TCR/CD3 and cytokine stimulation in contrast to CD8-γδ T cells. We conclude that γδ T cells in BM grafts are reshaped by donor CMV serostatus and highlight the potential adaptive role of CD8+γδ T cells in HCMV immune response.